2016
DOI: 10.1177/1524839916650865
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Teacher Knowledge, Dissemination Preferences, and Classroom Management of Student Concussions: Implications for Return-to-Learn Protocols

Abstract: In general, teachers were able to recognize the more commonly experienced concussion symptoms as well as management strategies. However, they appear to want greater concussion information and training. Given the daily influence of teachers on student tasks involving cognitive exertion, incorporation of formal concussion education for teachers is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…Researchers have discovered that school staff 37‐42 and medical providers 43‐46 have varying knowledge or efficacy when it comes to student concussion management. Therefore, a concerted statewide, department of education endorsed effort to train school staff on aspects of Return to Learn concussion management would be beneficial.…”
Section: Implications For School Healthmentioning
confidence: 99%
“…Researchers have discovered that school staff 37‐42 and medical providers 43‐46 have varying knowledge or efficacy when it comes to student concussion management. Therefore, a concerted statewide, department of education endorsed effort to train school staff on aspects of Return to Learn concussion management would be beneficial.…”
Section: Implications For School Healthmentioning
confidence: 99%
“…8, 10 -15 In more than one-fifth of schools, there is no clearly designated person managing RTL, and coordination among educators after injury is reported absent in nearly 80% of cases. 8,10,15 To align school procedures with bestpractice recommendations, national variability in RTL practices should be reduced and a minimum standard of care established. 2, 16 -20 One potential avenue for catalyzing these needed changes may be the revision of state concussion laws to include RTL guidance, as research suggests that state laws governing school health issues can influence patterns of behavior, resource allocation, and student outcomes.…”
mentioning
confidence: 99%
“…Other studies have shown that only 12% of teachers reported feeling "very knowledgeable" about concussion and desired more formal training on topics related to concussion. 19 Increasing disclosure of concussion for middle school youth is of particular interest moving forward for several reasons. First, middle school youth participate in scholastic and nonscholastic sports in greater numbers than high school age youth.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that only 12% of teachers reported feeling “very knowledgeable” about concussion and desired more formal training on topics related to concussion. 19…”
Section: Discussionmentioning
confidence: 99%